Value relevance and corporate social responsibility disclosure: A literature review - Diajeng Fitri Wulan (Lighthouse Publishing, 2022)
This article presents a review of the research literature that discusses the relevance of the value of CSR disclosure conducted in various research before. The popularity of the topic of value relevance today is still a hot topic of discussion among researchers, even though there have been many studies that have discussed value relevance analysis. This phenomenon is caused because there is much stigma regarding the discussion of whether CSR disclosure does have a relevant value or not. The literature review is limited to research conducted from 2020 to 2022 using reputable and credible articles. This article discusses the evidence for the value relevance phenomenon. The results of this article indicate that there are still differences in the research results that discuss the relevance value of CSR disclosure. There are several companies with good enough CSR disclosure to have a high relevance value, but there are also companies with the opposite result. This result can be caused by various influencing factors such as the ability of CSR disclosure owned by each company, the ability of the board of directors to regulate and make policies regarding CSR, research samples, political conditions, and assumptions and stigma on investors in certain areas. Further research is expected to expand the scope of research to provide arguments regarding the value of relevance more accurately.